Aircraft assembly process design for complex systems installation and test integration. - Li, Tao (Cranfield University, 2019)
The assembly line planning process connects product design and manufacturing through translating design information to assembly integration sequence. The assembly integration sequence defines the aircraft system components installation and test precedence of an assembly process. From a systems engineering view point, this activity is part of the complex systems integration and verification process. At the early conceptual design phase of assembly line planning, the priority task of assembly process planning is to understand product complexities in terms of systems interactions, and generate the installation and test sequence to satisfy the designed system function and meet design requirements. This research proposes to define these interactions by using systems engineering concept based on traceable RFLP (Requirement, Functional, Logical and Physical) models and generate the assembly integration sequence through a structured approach. A new method based on systems engineering RFLP framework is proposed to generate aircraft installation and test sequence of complex systems. The proposed method integrates aircraft system functional and physical information in RFLP models and considers these associated models as new engineering data sources at the aircraft early development stage. RFLP modelling rules are created to allow requirements, functional, logical and physical modes be reused in assembly sequence planning. Two case studies are created to examine the method. Semi- structured interviews are used for research validation. The results show that the proposed method can produce a feasible assembly integration sequence with requirements traceability, which ensures consistency between design requirements and assembly sequences.
Keywords: Assembly line design; assembly process planning; complex systems integration; RFLP modelling; requirement traceability; verification